Pengaruh Intensitas Radiasi terhadap Unjuk Kerja Kolektor Surya Tipe Vcorrugated dengan Penambahan Dimple Balls Posisi Stagger - Muhammad Robbi Solikhin; Mohamad Hakam; Priyambodo Nur Ardi Nugroho (Proceedings Conference On Design Manufacture Engineering And Its Application, 2022)
Solar collector use solar heat as heat energy. The heat energy, used for heating and drying. The air of heater consists absorber plate that absorbs solar radiation, channel through the air flows, and transparent cover. In this study, the solar collector was given the addition of obstacles and dimple balls, it could be applied to the absorber plate in the stagger position. This study determined effects of radiation intensity on Vcorrugated performance type solar air heater collector with addition of obstacles and dimple balls on absorbent plate. This research conducted using experimental method with 12mm diameters dimple balls with 0.5L dimple distances from the obstacle. The highest (thermo) energy value is 718.9 Watt/m2 intensities radiation, which is 59.108 Watt, while the highest (design) energy value is 718.9 Watt/m2 intensities radiation, which is 67.363 Watt. The highest (thermo) efficiency value is 64.1% at 431.373 Watt/m2 intensities, while the highest efficiency (design) value is 59% at 431.373 Watt/m2 intensities. This proved the value of efficiency is directly proportional to the heat received by the air and inversely proportional to the intensity of the radiation received, while the value of useful energy is directly proportional to the intensity of the radiation received.